2022
DOI: 10.1038/s41598-022-10458-8
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis mutant deficient in phosphatidylinositol-4-phosphate kinases ß1 and ß2 displays altered auxin-related responses in roots

Abstract: Phosphatidylinositol 4-kinases (PI4Ks) are the first enzymes that commit phosphatidylinositol into the phosphoinositide pathway. Here, we show that Arabidopsis thaliana seedlings deficient in PI4Kβ1 and β2 have several developmental defects including shorter roots and unfinished cytokinesis. The pi4kβ1β2 double mutant was insensitive to exogenous auxin concerning inhibition of root length and cell elongation; it also responded more slowly to gravistimulation. The pi4kß1ß2 root transcriptome displayed some simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Among these, 79 were differentially expressed in pi‐4kβ1, 2 mutants, 183 implicated as being regulated by WUS , HAN and/or GRF1 via differential expression and/or promoter binding, and 62 appear in the region of overlap as being regulated by WUS / HAN / GRF1 and the P14Kβ family (Fig. 6; Zhang et al ., 2013; Ma et al ., 2019; Piya et al ., 2020; Starodubtseva et al ., 2022). RWR scores were computed with WUS as a seed node and displayed two clusters, where genes in the cluster with greater scores have direct connections to WUS and others do not (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these, 79 were differentially expressed in pi‐4kβ1, 2 mutants, 183 implicated as being regulated by WUS , HAN and/or GRF1 via differential expression and/or promoter binding, and 62 appear in the region of overlap as being regulated by WUS / HAN / GRF1 and the P14Kβ family (Fig. 6; Zhang et al ., 2013; Ma et al ., 2019; Piya et al ., 2020; Starodubtseva et al ., 2022). RWR scores were computed with WUS as a seed node and displayed two clusters, where genes in the cluster with greater scores have direct connections to WUS and others do not (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PI‐4Kβ1 (homolog of Potri.007G109000) is believed to affect SA (Janda et al ., 2014; Šašek et al ., 2014) via biosynthesis of phosphoinositides, which function as cofactors for enzymes involved in membranes and vesicles responsible in part for signaling molecule transport (Mayinger, 2012; Starodubtseva et al ., 2022). In addition to regulating levels of SA itself, phosphoinositides may regulate the action of downstream SA‐signaling genes, which are highly represented among targets of the phosphoinositide‐dependent phospholipase C (Kalachova et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production and accumulation of PI-4,5-P 2 is a characteristic of the plant response to salicylic acid [ 99 ]. Conversely, Arabidopsis plants mutated in some PI4Ks constitutively accumulate SA [ 100 ], while displaying altered auxin-related responses independently of SA accumulation [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…pi4kβ1,2 plants display autoimmunity-associated dwarfism and enhanced resistance against bacterial and oomycete pathogens (Janda et al 2014 ; Šašek et al 2014 ; Antignani et al 2015 ; Thulasi Devendrakumar et al 2023 ). In addition to displaying autoimmunity and dwarfism, pi4kβ1,2 seedlings also grow shorter roots with abnormal root hairs (Preuss et al 2006 ; Šašek et al 2014 ; Starodubtseva et al 2022 ; Thulasi Devendrakumar et al 2023 ). Through reverse genetic analysis it has been shown that the defense hormone salicylic acid (SA) and Enhanced Disease Susceptibility 1 ( EDS1 ), a central component required for ETI, are both contributing to pi4kβ1,2 ’s autoimmunity (Šašek et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%